Primeiro registro de predação da praga de cajueiro Cicinnus callipius Schaus, 1928 (Lepidoptera: Mimallonidae) por vespas sociais (Hymenoptera: Vespidae) - Pires, Endson N. S.; Santos, Luan V. B.; Maciel, Tatiane T.; Barbosa, Bruno C. (Entomological Communications, 2023)
Social wasps are recognized for their important role as controllers of agricultural and urban pests and for their preference for preying on caterpillars. The present work describes, for the first time, the record of the social wasp Chartergellus communis Richards, 1978 (Hymenoptera: Vespidae) preying on Cicinnus callipius Schaus, 1928 (Lepidoptera: Mimallonidae), a defoliator caterpillar, pest of cashew trees. The record took place in a fragment of Semideciduous Seasonal Forest in the municipality of Altos, Piauí, Brazil, close to a cashew plantation. Since wasps can travel up to 300 m in search of prey, the conservation of colonies close to cultivation areas is of paramount importance. For this, environmental education actions are necessary in order to promote the awareness of the population and, mainly, of the producers and workers of the plantations.